FGFR1 mediates recombinant thrombomodulin domain-induced angiogenesis. (11th November 2014) - Kuo, Cheng-Hsiang; Sung, Meng-Chen; Chen, Po-Ku; Chang, Bi-Ing; Lee, Fang-Tzu; Cho, Chia-Fong; Hsieh, Tai-Tzu; Huang, Yu-Ching; Li, Yi-Heng; Shi, Guey-Yueh; Luo, Chwan-Yau; Wu, Hua-Lin
Abstract: Aims: The recombinant epidermal growth factor-like domain plus the serine/threonine-rich domain of thrombomodulin (rTMD23) promotes angiogenesis and accelerates the generation of activated protein C (APC), which facilitates angiogenesis. The aim of this study was to elucidate the molecular mechanisms underlying the angiogenic activity of rTMD23. Methods and results: We prepared rTMD23 and its mutants that did not possess the ability to promote APC generation and investigated their angiogenic activities in vitro and in vivo . rTMD23 mutants promoted proliferation, migration, and tube formation of human umbilical vein endothelial cells in vitro and induced neovascularization in vivo ; these effects were similar to those exerted by wild-type rTMD23. To investigate its interaction with rTMD23, Type I fibroblast growth factor receptor (FGFR1) was precipitated along with syndecan-4 by rTMD23-conjugated Sepharose in human umbilical vein endothelial cells and FGFR1-expressing human embryonic kidney 293 cells. Additionally, the kinetics of the interaction between rTMD23 and FGFR1 were analysed using surface plasmon resonance. rTMD23-induced FGFR1 activation and tube formation were inhibited by an FGFR1-specific tyrosine kinase inhibitor, PD173074, or by knockdown of FGFR1 using siRNA technology. We observed an improvement in rat hindlimb recovery in an ischaemic model following rTMD23 treatment, and this was associated with increased neovascularization and FGFR1 phosphorylation. Conclusion: rTMD23 induced angiogenesis via FGFR1, a process that is independent of the APC pathway.